Student Perceptions of Using Spotify for Podcasters as a Storytelling Media - Yuniarti (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Spotify for Podcasters has emerged as a popular platform for podcast creation. However, its application in early childhood learning requires further exploration. This research aims to analyze the potential and challenges of using the Spotify for Podcasters application as a media storytelling tool in early childhood education. The research employs a mixed-method sequential explanatory approach, combining qualitative and quantitative methods. The study involves students from the Early Childhood Education program enrolled in the Language Development and Storytelling Skills course. Qualitative data collection methods include observation and interviews, while quantitative data are obtained through structured surveys to assess students' perceptions of the application's usage. Results indicate that using Spotify for Podcasters significantly enhances students' storytelling abilities. It helps sharpen skills such as clear pronunciation, appropriate intonation, and word choice. Moreover, the application enables the creation of interactive and engaging stories for a young audience. However, the study also identifies challenges. Students initially faced technical difficulties using the application, including bugs and limitations in accessing Spotify accounts. Storage capacity limitations within the app posed challenges in managing podcast content. The implications suggest that Spotify for Podcasters can improve students' storytelling skills and facilitate more engaging early childhood learning. However, initial training and strategic thinking are necessary to address emerging constraints. This research provides valuable insights into the potential and challenges of utilizing podcasting technology in early childhood education, laying the groundwork for further developments in this field.